Функційно-семантична специфіка префіксальних новотворів із компонентом анти- у мові інтернет-видань - Левчук, Ірина; Levchuk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено аналіз префіксального словотворення інновацій з компонентом анти- у мові сучасних ЗМІ на базі інтернет-видань. Виявлено загальномовні тенденції та оказіональні явища, з’ясовано їх функційно- семантичну специфіку. Розглянуто вживаність у мові ЗМІ лексем з компонентом анти-, які вже ввійшли в лексикографічну практику сьогодення, та особливості послуговування новотворами цього типу, які досі не зафіксовано в академічних лексикографічних працях. З’ясовано, що інноваційні одиниці з компонентом анти- виконують не тільки номінативну функцію, а й позначені істотною стилістичною маркованістю.An analysis of the formations of prefixed neologisms containing the component anti- has been carried out with reference to the language used in modern mass media publications. General language patterns and phenomena have been identified. Their functional and semantic peculiarities have been described. The usage of the words containing the component anti- in the language of mass media has been investigated. In this paper attention is devoted both to lexemes which are already recorded in dictionaries and to those which cannot be found in academic dictionaries. It has been demonstrated that innovative words containing the component anti- not only perform a nominative function but that they also possess a degree of stylistically colouring.
Functional and Semantic Peculiarities of Newly-coined Words Containing the Prefix anti- in the Language of Internet Publications.
Keywords: префіксальне словотворення; префіксальний новотвір; префікс анти-; іменний дериват; мова ЗМІ; prefixational word-formation; prefixal neologisms; prefix anti-; noun derivative; mass media language